História da formação de professores em Cascavel entre 1951 e 1971: a trajetória das escolas normais Carola Moreira e Irene Rickli - Facchi, Jehnny Zélia Kalb (2013)
This research aims to study the teacher training in Cascavel (Paraná State, Brazil), between the years of 1951 and 1971, focusing Carola Moreira (1956-1968) Regional Normal School and Irene Rickli (163-1971) Normal High School. Around the goal, we bring up the following problem: What are the historical determinants that contributed to create the need for teacher training in Cascavel by Normal School? This question expresses the goal of analyzing the historical period and schools structuring of Cascavel, as well as to understand the political and pedagogical challenges faced by the teachers in that period, and also the school practices undertaken to face them. Our historical record is delimitated from 1951, because it was the political emancipation year of Cascavel, besides that, it was a period that was initiated an intense population migration to this region. The analysis reaches the year of 1971, when it occurred the education reform of Junior school and Secondary school level by the Law n.º 5.692, which extinguished the training teacher in the Normal modality and instituted the professional training of high school level, called “Teaching”. The aim is seeking to understand the historical essence of these Normal Schools and to reach this goal, we based the research in the analysis of documental sources, oral sources with the participation of 8 interviewed, among them 3 former teachers and 5 former elementary School teachers, pictures and printed materials in newspapers. The first chapter discusses the historical and legal aspects of the normal education in Brazil emphasizing the Organic Law of Normal Education of 1946, and the Law n.º 4.024/61 and in the Law n.º 5.692/71. In the second chapter, we seek to analyze the training teacher in the normal schools in the state of Paraná before and after the Organic Law for Normal Education, emphasizing the action of Erasmo Pilotto. Furthermore in this chapter we present the political, economic and social aspects of the municipality of Cascavel in order to understand the appearance of the need to establish normal schools. The third chapter enters in the history of the school institutions already mentioned seeking to explain their origin. The last chapter, finally, looks at the organization of Normal Schools, their pedagogical bases, the developed practices, as well as the conflicts and difficulties faced. The research found that both schools had their origins in an articulated process between the needs of local elite, which saw the schooling as fundamental element to maintain while elite and in the state policies of establishing these schools as propeller elements of developing and social control. We sought to show that despite the normal schools have been a victory for all the society of Cascavel, they are much more for the class that enjoyed of them first, because from the first groups came out the municipal educational planning.